(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
Offered for the first time in 2022 within the scope of the Fashion Colloquium, the Working Group (WG) named Fashion: Between Productions and Thoughts, contributes to the field of fashion studies, by being a non-disciplined space for reflection on fashion as an expanded field, encompassing aspects linked to its material production, commercialization, but also to the construction of ways of living and ways to the distribution of the sensible. In this interview, the coordinators Professor Doctor Larissa Almada and Professor Doctor Guido Conrado mention important factors that make up the idea of the respective GT.